Research on improving the construction of cultivation quality assurance system of postgraduates - ZHU Yulei, WANG Yanling, ZHENG Kai, QIU Shuang, LI Lu, LIU Laikui (Kouqiang yixue)
Objective During the rapid expansion of postgraduate education, it is meeting more and more conflicts between enrollment scale and cultivation quality. The construction of a cultivation quality assurance system for postgraduates becomes an urgent task in the new situation. Methods The data was analyzed with SPSS 24.0, based on the anonymous review results of postgraduates’ dissertations by a three-A stomatological hospital during 2022-2023. Results The results showed that the overall evaluation of anonymous dissertation opinions in 2022 was better than that in 2023, and the passing rate of anonymous dissertation evaluation of doctoral students was higher than that of master students. Irregular forms of composition, low research workload, and insufficient innovation were found in failed postgraduates’ dissertations. Conclusion Strengthening the management of study style education and training process, and exploring cultivating mode of overlapping subjects, are necessary to improve the construction of cultivation quality assurance system of postgraduates.